DARI MANTRI HINGGA DOKTER JAWA: STUDI KEBIJAKAN PEMERINTAH KOLONIAL DALAM PENANGANAN PENYAKIT CACAR DI JAWA ABAD XIX - XX - . Baha'uddin (Humaniora, 2006)
This paper describes health service in Java society in the past (in nineteenth and early twentieth century), especially about the colonial government policy to handle smallpox cases. It seems that the success of this policy depends on the role of mantri and dokter djawa. The emotional and cultural propinquity between Java society and mantra and and dokter Jawa was the key success of smallpox vaccination. Mantri and dokter Jawa also attempted to expand the access of curative care from hospitals to the native society.